2021
DOI: 10.2320/matertrans.l-m2021828
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analyses of Wavy Interface Formation and Local Melting Phenomena at the Magnetic Pulse Welded Al/Fe Joint Interface

Abstract: A 1050-O aluminum plate and a low carbon steel (SPCC) plate were seam welded by magnetic pulse welding (MPW). Experimental and numerical analysis methods were combined to investigate the wavy interface formation and local melting phenomena at the Al/Fe joint interface. The metallographic observation results showed that Al/Fe joint interface presents a trigger-like wave shape with two types of intermediate layers intermittently formed at the interface. Collision angle between two plates and impact velocity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…investigated the magnetic pulse welded Al/steel interface using both experimental and numerical analyses and reported the temperature change at the welding interface. 24,25) These reports showed that at the welding interface, the temperature rises above the melting point of base metal and then cools rapidly. In addition, the dendritic structure at welding interface was reported in the joints formed by using explosive welding which is a kind of the impact welding method, and it is concluded that the formation of the dendritic structure resulted from local melting and successive solidification.…”
Section: Microstructure Of Strong Welding Interfacementioning
confidence: 99%
“…investigated the magnetic pulse welded Al/steel interface using both experimental and numerical analyses and reported the temperature change at the welding interface. 24,25) These reports showed that at the welding interface, the temperature rises above the melting point of base metal and then cools rapidly. In addition, the dendritic structure at welding interface was reported in the joints formed by using explosive welding which is a kind of the impact welding method, and it is concluded that the formation of the dendritic structure resulted from local melting and successive solidification.…”
Section: Microstructure Of Strong Welding Interfacementioning
confidence: 99%